Nuclear Energy: A Professional Assessment - Watt Committee on Energy Publications (Spon, 2013)
At a number of meetings of the Watt Committee Executive, I mentioned my embarrassment at being askedrepeatedly by all sorts of people, |(3z|(BWhat does The Watt Committee on Energy think about nuclear energy?|(3y|(BAt the Executive meeting on 20 October 1981, Mr G.K.C. Pardoe, our Deputy Chairman, suggested ananswer: we should form a working party to produce a summary of the position, all the way from the uraniummine to the disposal of nuclear waste. It would be as professional and objective as the time availablepermitted. It would deal with the question from the British standpoint a similar text produced.